La gestión económica de Emilio Lissón al frente de la arquidiócesis de Lima en la década de 1920 - Ara Goñi, Jesús Angel (2013)
The aim of this paper is to demonstrate that, due to Archbishop Emilio Lissón's economic management, the Archdiocese of Lima’s financial situation was very difficult at the end of the 1920s. Owing to this, Vatican authorities gradually reduced the Archbishop’s powers in the administration of Church property, and in January 1931 ordered him to resign. The main sources that were used in this study are balance sheets and correspondence from both the Archbishopric of Lima and Vatican Secret Archives.